EFFORTS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN OVERCOMING STUDENTS' DIFFICULTIES IN READING AND WRITING THE QURAN AT SD AL-ITTIHADIYAH LAUT DENDANG - Jumi Laila Nurzannah; Khairuddin (RADJA PUBLIKA, 2026)
In an effort to improve the ability to read and write the Qur'an in students, it cannot be separated from the efforts of teachers. Where this is a process of maturing students through learning to optimize the potential that exists in students so that character, character and personality are formed, where this requires a holistic strategy so that the learning process can run optimally. Where the role of Islamic Religious Education teachers is very important in forming a strategy, building conducive interactions to overcoming the impact of difficulties in reading and writing the Qur'an among students. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, in-depth interviews, and documentation. Research findings describe new information obtained from the research process, which is based on data collection that makes it knowledge